Suprachiasmatic Nucleus Neuropeptide Expression in Patients with Huntington's Disease - van Wamelen, Daniel J.; Aziz, N. Ahmad; Anink, Jasper J.; van Steenhoven, Robin; Angeloni, Debora; Fraschini, Franco; Jockers, Ralf; Roos, Raymund A. C.; Swaab, Dick F. (Sleep (New York, N.Y.), 2013)
To study whether sleep and circadian rhythm disturbances in patients with Huntington's disease (HD) arise from dysfunction of the body's master clock, the hypothalamic suprachiasmatic nucleus. Postmortem cohort study. Eight patients with HD and eight control subjects matched for sex, age, clock time and month of death, postmortem delay, and fixation time of paraffin-embedded hypothalamic tissue. Using postmortem paraffin-embedded tissue, we assessed the functional integrity of the suprachiasmatic nucleus in patients with HD and control subjects by determining the expression of two major regulatory neuropeptides, vasoactive intestinal polypeptide and arginine vasopressin. Additionally, we studied melatonin 1 and 2 receptor expression. Compared with control subjects, the suprachiasmatic nucleus contained 85% fewer neurons immunoreactive for vasoactive intestinal polypeptide and 33% fewer neurons for arginine vasopressin in patients with HD (P = 0.002 and P = 0.027). The total amount of vasoactive intestinal polypeptide and arginine vasopressin messenger RNA was unchanged. No change was observed in the number of melatonin 1 or 2 receptor immunoreactive neurons. These findings indicate posttranscriptional neuropeptide changes in the suprachiasmatic nucleus of patients with HD, and suggest that sleep and circadian rhythm disorders in these patients may at least partly arise from suprachiasmatic nucleus dysfunction.